Gestión de ventas en “Ferretería Cando” del cantón Ventanas durante el periodo 2023. - Sánchez Zapata, Evelyn Antonella (2024)
Sales management at Cando Hardware is differentiated by a series of fundamental elements that contribute to the success and effectiveness of its operations. These elements, taken together, guarantee that the company can achieve its commercial goals and take into account its customers' requests effectively. Currently effective sales management is decisive for the success of any business, this tactic can be fundamentally effective in keeping consumers satisfied and achieving business objectives. Cando Hardware is committed to maintaining an orderly and diverse inventory, which allows us to show a wide range of products to customers and thus prevent a decrease in sales. Customer service is another fundamental factor that the company will be in charge of correcting, to improve the customer's purchasing experience. The team will be well trained to provide exceptional service, answer customer questions and assist them in making decisions about their purchases. Technology plays an essential role in the sales management of Cando Hardware, which is why the aim is to improve the accounting system and inventory management. At the same time, make the most of social networks by showing our wide variety of products, through strategically designed advertising in order to attract new customers to the Hardware Store. Effective sales management is based on several essential pillars. These include constant product availability, exceptional customer service, implementation of advanced technology, a robust pricing strategy, optimized logistics and comprehensive data analysis. The synergy of these elements ensures that the company maintains its competitive position in the dynamic retail market.